Development and user evaluation of an immersive light field system for space exploration - Goriachev, Vladimir; Kuula, Timo; Tikka, Petri; Karjalainen, Jaakko; Helin, Kaj (Frontiers in Virtual Reality, 2024)
This paper presents the developmental work and user evaluation results of an immersive light field system built for the European Space Agency’s (ESA) project called “Light field-enhanced immersive teleoperation system for space station and ground control.” The main aim of the project is to evaluate the usefulness and feasibility of light fields in space exploration, and compare it to other types of immersive content, such as 360° photos and point clouds. In the course of the project, light field data were captured with a robotically controlled camera and processed into a suitable format. The light field authoring process was performed, and a light field renderer capable of displaying immersive panoramic or planar light fields on modern virtual reality hardware was developed. The planetary surface points of interest (POIs) were modeled in the laboratory environment, and three distinct test use cases utilizing them were developed. The user evaluation was held in the European Astronaut Centre (EAC) in the summer of 2023, involving prospective end-users of various backgrounds. During the evaluation, questionnaires, interviews, and observation were used for data collection. At the end of the paper, the evaluation results, as well as a discussion about lessons learned and possible improvements to the light field system, are presented.